Dynamic modeling of flow management as a tool for improving organizational and technological solutions and sustainable development in civil engineering - PASTUKHOVA, Susanna; ARUTIUNIAN, Iryna (Ways to Improve Construction Efficiency, 2025)
The article thoroughly examines the problematic issues of ensuring designed energy efficiency of civil buildings directly at the construction stage by improving organizational and technological solutions. Traditional approaches to construction flow management are analyzed in detail, and key reasons for the "gap" between calculated and actual energy consumption are identified, which lie in uncontrolled technological deviations, logistical delays, and organizational downtime. Special attention is paid to the development of mathematical tools for an optimization model based on system dynamics methods and flow management principles. A system of controlled variables and an objective function for minimizing integral energy costs have been established, formalizing the direct correlation between the duration of work, non-productive time losses on-site, and the total energy costs of construction and subsequent operation. The research results, verified through a computational experiment, prove the advantage of industrialized assembly and flow-parallel organization of work. The application of the optimized model allowed for reducing energy costs at the construction stage from 420 to 310 MWh, decreasing the total duration of work from 14 to 11 months, and significantly increasing the integral efficiency criterion of organizational and technological solutions (from 0.84 to 1.11). Ultimately, it is proven that dynamic modeling of flow management transforms scheduling from a time-control tool into a scientifically grounded mechanism for guaranteeing an object's energy efficiency, which is critical for achieving sustainable development goals in modern civil engineering.